PERILAKU KONSUMSI SWIKE KODOK PADA MASYARAKAT MUSLIM DI KABUPATEN GROBOGAN - Widayanti, Safira; Pujiyono, Arif (Diponegoro Journal of Islamic Economics and Business, 2021)
Consumption Behavior of Swike Kodok in Muslim Communities in Grobogan District. Every muslim should understand about Islamic laws. One of them is Islamic dietary law about halal (permissible) or haram (forbidden) food of swike kodok. Although swike kodok is haram food, some Muslims prefer to continue consuming it. This study aims to determine the reasons of several Muslims who continue consuming swike kodok. This study uses the phenomenological method with the Interpretative Phenomenological Analysis (IPA) approach. The Interpretative Phenomenological Analysis (IPA) approach is used in research to find out the meaningful and different experiences on every Muslim consumer of swike kodok. This method uses in-depth interview techniques and analyzed as stages in the phenomenological method guidelines with the Interpretative Phenomenological Analysis (IPA) approach. Participants in this study were 5 Muslim consumers of swike kodok. They are native inhabitants of Grobogan district that also swike kodok stalls consumers, in Purwodadi sub-district. The results obtained from this study there are 4 main themes and at once reveal the background of the phenomenon why Muslims still consuming swike kodok. Among them are social environment, addictive behavior of consuming swike kodok, the satisfaction of consuming swike kodok, and self- belief.